Analisa Ekonomi Media Radio Gen 103,1 FM - Laras Puspitorini (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
As conventional media, radio must be able to adapt and innovate to continue to attract audiences and maintain its business. One that is considered capable of adapting in the era of digitalization is Gen 103.1 FM, a radio in Surabaya managed by PT. Mahaka Radio Integra Tbk. Based on Nielsen data in January 2023, Gen FM has the largest exclusive listeners compared to other radio stations with the